Conducta Obstétrica ante Corioamnionitis en primigesta de 19 años con embarazo de 33 semanas. - Barrera Hurtado, Stephanie Liseth (2021)
Chorioamnionitis is an infection that can occur in pregnancy, affecting the placenta, amniotic fluid and the membranes that surround the fetus. The main cause is the bacteria found in the vagina and that migrate to the uterus, causing this pathology to occur more frequently when there is premature rupture of membranes long before birth and is associated with greater maternal and neonatal morbidity and mortality, especially in preterm infants. For this reason, we present the clinical case of a 19 years old primiparous patient, referred from the first level for presenting premature rupture of membranes of more or less 4 days of evolution that later evolves to Chorioamnionitis. This document presents the management and follow-up of this case together with the evolution of the patient, a work carried out by health professionals, with correct decisions and measures for Chorioamnionitis and preterm pregnancy, in order to preserve the health of the patient mother-child binomial.